Current management options in metastatic renal cell cancer - Sittu Govindasamy Dinakaran Gangadaran (Frontiers Media S.A., 2017)
Renal cancer accounts for 2.4% of all cancers. Localised disease accounts for the majority of renal cancers (70-75%), however 20-25% of these ultimately develop distant metastasis. The median overall survival of un treated metastatic disease is 5 months with 1-year survival of only 29%. The management of metastatic renal cell cancers traditionally relied on systemic immunotherapy with attendant high morbidity but after the year 2005 the use of effective targeted therapy with tolerable side effect profile has improved the survival from 10.2 months in the cytokine era to 17.7 months. This article reviews the past, present and future options in the management of metastatic renal cancer.